Promosi Wisata Religi dan Budaya Situs Sanghyang Permana Balaniksa Kawasen di Desa Bojongmengger Melalui Media Sosial Instagram - Hamdan Ihwani; Maghfiroh Indah Pratiwi; Pipih Sopiah; Kiki Endah; Roni Supriatna (Lembaga Pengembangan Kinerja Dosen, 2024)
The Sanghyang Permana Balaniksa site is one of the historical remains of the Galuh Pangauban Kingdom. The Sanghyang Permana Prabudigaluh Salawe site is one of the historical relics of the Galuh Pangauban Kingdom. This research outlines efforts to promote religious and cultural tourism at the site, which also acts as an educational resource and cultural destination. This study used descriptive qualitative method. Promotion of religious and cultural tourism at Sanghyang Permana Balaniksa with the hope of increasing visitors and becoming better known to the public, one of which is using the social media Instagram. Promotion uses new breakthroughs to increase attractiveness, where social media becomes an effective and efficient tool for promoting culture in the region. Using social media requires creativity in terms of composition and sentence structure that attracts social media users. It is hoped that promotion via Instagram can be significant in increasing public interest in visiting the Sanghyang Cipta Permana Site in Bojongmengger Village.